Caspofungin Induced Cell Wall Changes of Candida Species Influences Macrophage Interactions - Walker, Louise A.; Munro, Carol A. (Frontiers in Cellular and Infection Microbiology, 2020)
Candida species are known to differ in their ability to cause infection and have been shown to display varied susceptibilities to antifungal drugs. Treatment with the echinocandin, caspofungin, leads to compensatory alterations in the fungal cell wall. This study was performed to compare the structure and composition of the cell walls of different Candida species alone and in response to caspofungin treatment, and to evaluate how changes at the fungal cell surface affects interactions with macrophages. We demonstrated that the length of the outer fibrillar layer varied between Candida species and that, in most cases, reduced fibril length correlated with increased exposure of β-1,3-glucan on the cell surface. Candida glabrata and Candida guilliermondii, which had naturally more β-1,3-glucan exposed on the cell surface, were phagocytosed significantly more efficiently by J774 macrophages. Treatment with caspofungin resulted in increased exposure of chitin and β-1,3-glucan on the surface of the majority of Candida species isolates that were tested, with the exception of C. glabrata and Candida parapsilosis isolates. This increase in exposure of the inner cell wall polysaccharides, in most cases, correlated with reduced uptake by macrophages and in turn, a decrease in production of TNFα. Here we show that differences in the exposure of cell wall carbohydrates and variations in the repertoire of covalently attached surface proteins of different Candida species contributes to their recognition by immune cells.